2017
DOI: 10.1016/j.str.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Environment Induces Dimerization and Ligand Binding Site Collapse in the Vps10p Domain of Sortilin

Abstract: Sortilin is a neuronal receptor involved in transmembrane signaling, endocytosis, and intracellular sorting of proteins. It cycles through a number of cellular compartments where it encounters various acidic conditions. The crystal structure of the sortilin ectodomain has previously been determined at neutral pH. Here, we present the 3.5-Å resolution crystal structure of sortilin at pH 5.5, which represents an environment similar to that of late endosomes, where ligands are released. The structure reveals an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…Therefore, the pH at the cellular compartments containing Sortilin dramatically changes during Sortilin trafficking in cells. Consistent with the findings of the most recent studies [25,26], we also demonstrated that sSortilin dimerizes under a low pH buffer condition. In addition, SEC analysis revealed that the A495E mutant in mouse Sortilin, which is located in the vicinity of F128 at the hydrophobic loop, abolishes the potency of pH-dependent dimerization [26].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, the pH at the cellular compartments containing Sortilin dramatically changes during Sortilin trafficking in cells. Consistent with the findings of the most recent studies [25,26], we also demonstrated that sSortilin dimerizes under a low pH buffer condition. In addition, SEC analysis revealed that the A495E mutant in mouse Sortilin, which is located in the vicinity of F128 at the hydrophobic loop, abolishes the potency of pH-dependent dimerization [26].…”
Section: Resultssupporting
confidence: 93%
“…Consequently, our structure could clearly represent the contribution of E455 to the hydrophobic interaction with F137 in Sortilin dimerization at acidic pH. The conformational changes that were observed upon dimerization, as revealed through structural comparison with human sSortilin, were also confirmed independently in these recent studies [25,26], indicating the importance of conformational changes for dimerization of sSortilin at acidic pH.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations